Delayed surgical infections. - Piñeyro, Alberto; Carriquiry, Luis; Misa, Carlos; Lanz, Gabriel (Cirugía del Uruguay, 1987)
Seven cases of deiayed surgical infections are presented, considering as such, those thal occur more than six months alter surgery. lt is suggested that the majority of these infections are caused by microorganisms introduced al the time of the operatlon and that they are made evidenl as a result of alterations in the host's defensive mechanisms.